Bibliometric analysis of Bangladesh Journal of Obstetrics and Gynecology (BJOG), 2008 – 2018 (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
In the last 20 years Bangladesh has addressed maternal health and child mortality most importantly, which has reduced the rate 63% successfully. Bangladesh Journal of Obstetrics and Gynecology (BJOG) is a reputed journal of Bangladesh published by the specialized association Obstetrical and Gynecological Society of Bangladesh (OGSB). This study is the first attempt to evaluate a Bangladeshi medical journal applying the bibliometric analysis method. Though the journal existed from 1999, a total of 284 articles were found in the archive of BanglaJOL in the latest 11 volumes. Each issue published 13.52 articles on average, predominantly 180 (63.38%) in joint authorship with an average degree of collaboration of 0.63. The pattern of collaboration has been visualized in clusters using Vosviewer. Majority of contributors were local where BSMMU as an institution and Saleha Begum Chowdhury as author ranked at the top. Finally, the article that received the highest number of citations was titled “Maternal and fetal outcome of eclamptic patients in a tertiary hospital”. In this article, the most occurring keyword was ‘pregnancy’ occurred 11 times; however, like majority OBGYN journals, topics like ‘preeclampsia’ and ‘endometriosis’ have also focused in this article following the global trend. Most importantly, the joint authorship trend is getting among the authors.Bangladesh J Obstet Gynaecol, 2021; Vol. 36(2): 89-100